Mildly Higher Serum Prolactin Levels Are Directly Proportional to Cumulative Pregnancy Outcomes in in-vitro Fertilization/Intracytoplasmic Sperm Injection Cycles - Zhang, Duoduo; Yuan, Xi; Zhen, Jingran; Sun, Zhengyi; Deng, Chengyan; Yu, Qi (Frontiers in Endocrinology, 2020)
Hyperprolactinemia has long been considered as a detrimental factor fertility due to anovulation. Whether mild hyperprolactinemia should be corrected before initiating an IVF/CISI cycle has not been explained clear. We aim to figure out how different levels of prolactin affect IVF outcomes. 3009 patients with basal prolactin < 50ng/mL undergoing IVF/ICSI cycles were recruited in the study. Pregnancy outcomes were compared between patients with basal prolactin levels > and ≤ the median level (16.05 ng/mL). Multifactor analyses were carried out among four sub-groups divided by different prolactin levels. A repeated analysis of variance was used to explore the relationship between the ascending trend of PRL levels over ovarian stimulation and the corresponding cumulated pregnancy outcomes. There were significantly more oocytes (9 vs 8, P=0.013) and embryos (6 vs 5, P=0.015) in patients with basal prolactin>16.05ng/mL. Basal prolactin＞30ng/mL was positively related to cumulated clinical pregnancy and ＞40ng/mL was a good indicator for cumulated live birth rate. Throughout ovarian stimulation, prognosis of pregnancy improved with increasing PRL levels. Patients with better cumulated pregnancy outcomes had significantly higher PRL levels as well as a profound increasing trend during the stimulating process than those of patients not conceived. For patients underwent GnRH agonist long protocol IVF/ICSI treatment，a slightly higher PRL level during COH is a beneficial indicator for cumulated pregnancy/live birth rates.